Access to rideshare and satisfaction, prenatal healthcare utilisation, and preterm delivery among pregnant Medicaid recipients: A randomised controlled trial. Issue 3 (13th December 2022) - Lynch, Courtney D.; Conroy, Sara; Jackson, Kenneth A.; Smith, Rachel M.; Hade, Erinn M.
Abstract: Background: Lack of access to reliable transportation is a barrier to timely receipt of prenatal care. Objectives: We aimed to assess the impact of modernisation of non‐emergency medical transportation services on patient satisfaction, prenatal care utilisation, and preterm delivery. Methods: We conducted a randomised controlled pilot trial among pregnant Medicaid recipients in Franklin County, Ohio, a county with high rates of infant mortality. Individuals were randomly assigned to usual non‐emergency medical transportation services or enhanced smart transportation (EST) services (i.e. on‐demand transportation with access to a mobile application and trips to the grocery store, food bank or pharmacy). The primary outcome was satisfaction with transportation services. Secondary outcomes included adequacy of prenatal care utilisation (APNCU) and preterm delivery <37 weeks. Results: Women were screened between 31 May 2019 and 30 June 2020, with 143 being eligible and enrolling. Evidence of increased satisfaction with transportation was observed in the intervention group compared to usual transportation, with 83.8% and 68.8% reporting being somewhat satisfied or very satisfied respectively (risk difference [RD] 14.8%, 95% confidence interval [CI] 0.5, 29.1). There were no meaningful differences in APNCU or preterm delivery between groups (APNCU: RD 2.1%, 95% CI −14.0, 18.2 and preterm delivery: RD −3.9%, 95% CI −17.0, 9.3). Conclusions: We found evidence of increased transportation satisfaction among pregnant women randomly assigned to EST versus usual transportation. It remains unclear whether the provision of EST increases prenatal care utilisation or decreases preterm delivery.